Community Participation In Corporate Social Responsibility Program Arrangement - Ekawaty, Dian; Tamma, Sukri; Sesa, Muh. Alfatihah; Wijaya, Andika; Khairunnisa, Andini; Tangdi Alla, Alysyah Syahrani; Mustamin, Muhajirin (LP2M IAIN Palopo, 2025)
Corporate Social Responsibility (CSR) is a mandatory obligation for companies in Indonesia to balance economic, social, and environmental interests, particularly for communities living around production areas that often experience negative impacts from industrial activities such as air pollution, economic inequality, and health problems. This study aims to explain the extent of community involvement in CSR implementation in Biring Ere Village, Pangkep Regency. The research employed a qualitative method using interviews and observations conducted in 2025. The forms and levels of community aspirations were analyzed based on Arnstein's ladder of participation. The findings reveal that, in the early stages, community participation in CSR program planning was limited to village officials. However, there is now a growing trend of broader participation involving people from diverse backgrounds. These results indicate a shift toward a more participatory CSR model, which contributes to greater program effectiveness and sustainability for local communities.